Design thinking-learning and lifelong learning for employability in the 21st century - Vijayakumari Seevaratnam; Deanne Gannaway; Jason Lodge (Journal of Teaching and Learning for Graduate Employability, 2023)
Surviving and thriving in this 21st century volatile, uncertain, complex, and ambiguous (VUCA) world caused by rapid digitalisation and changing work landscape, requires agile organisations with agile employees who are adaptable, resilient, and actively engaged in lifelong learning. A blended workforce encompassing full-time and 'gig' employees, working in tandem with smart machines, calls for an innovative and collaborative workforce capable of critical thinking and creative problem solving. This paper aims to highlight the potential of design thinking approaches to foster lifelong learning and graduate employability in a VUCA environment. The paper outlines an empirical study investigating the multiple benefits of incorporating design thinking process attributes in higher education. It argues that such processes can result in the development of 21st century skills and mindset and graduate capability themes that promote lifelong learning skills. Incorporating such strategies offers the potential to narrow the competency gap between workforce and work and enhance the employability and career development of graduates. The paper offers a Framework for Lifelong Learning in a VUCA environment that outlines the powerful traits that arise as payoffs from engaging in and practising design thinking. This framework can serve as a preliminary guide for higher education educators, learning organisations and individuals to inculcate and enhance lifelong learning